Imaging the Anterior and Posterior Cruciate Ligaments. - Anagha P. Parkar (Journal of the Belgian Society of Radiology, 2016)
The anterior and posterior cruciate ligaments are important stabilizers of knee joint function. Although they are both similar in their native appearance, they possess slightly different properties and complement each other in function. The imaging findings differ between the anterior and posterior cruciate ligaments. MRI is the main modality, but also radiographs and CT has a role in pre- and post-operative imaging. The aim of this review is to present imaging findings of injured cruciate ligaments and pre-and post-operative imaging, to present and explain the potential pitfalls in cruciate ligament imaging.